Early Childhood Education Management: A Study on Effectual in Village Institutions of West Bengal, India - Chakraborty, Kaushik; Joyprokash Mondal (Santoso Academy Network, 2023)
The objective of this study is to discuss some methods that can be helpful for the development of Montessori as well as the Kindergarten Approach to Education. Our research work is based on an unstructured questionnaire and observation method. To imply adequate qualitative and quantitative data, we searched the goals and objectives of Kindergarten and Montessori education policy from local concerned institutions of West Bengal in India. Our field study was conducted on some villages of Midnapore and South 24 Parganas District of Bengal. Early childhood is a stage that requires an overall holistic development model. These two approaches deal with that, but there are some methods related to language and communication that can easily develop the quality of the approaches above. It is shown with projected lesson plans and timetable management. This study explores and discusses such methods and points out how these methods can bring changes to those approaches. This paper also inputs the Indian state education policy about it.